Odpowiedzi

2010-03-20T18:52:55+01:00
A)
0,83x+0,82=0,23x+1,52
0,83-0,23=1,52-0,82
0,70x=0,70 /0,70
x=1
b)
0,6x+2(0,1x-0,1) + 0,2(x+1)
0,6x+0,2x-0,2+0,2+0,2
0,8x=0,2 /0,8
x=0,25

c)
0,7(x+2)=0,4(x+1)+0,3x+1
0,7x+0,14=0,4x+0,4+0,3x+1
0,7x-0,7x=1,4-0,14 = 0

d)
0,15(2x+4)=2(1,3+0,3x)-0,6
0,30x+0,60=2,6+0,6x-0,6
0,3x=2 /0,3
x= 2* 10/3 = 20/3 = 6 2/3

e)
0,1(x+1)-0,05(3x-10)+0,4-0,35x
0,1x+0,1-0,15x+0,5+0,4-0,35x
-0,4x=-1 /-0,4
x=2,5
2010-03-20T19:12:09+01:00
0.83x+0.82=0,23x=1.52 /-0.23X
0.1x+0.82=1.52 / - 0.82
0.1x=0.7 /:0.1
X=7

0.6x+2(0.1x-0.1)+0.2(x+1)
2010-03-20T19:31:37+01:00
A)
0,83x+0,82=0,23x+1,52
0,83x-0,23x=1,52-0,82
0,6x=0,7
x=1⅙

b)
0,6x+2(0,1x-0,1) = 0,2(x+1)
0,6x+0,2x-0,2=0,2x+0,2
0,6x+0,2x-0,2x=0,2+0,2
0,6x=0,4
x=⅔

c)
0,7(x+2)=0,4(x+1)+0,3x+1
0,7x+1,4=0,4x+0,4+0,3x+1
0,7x-0,4x-0,4x-0,3x=1-1,4
-0,4x=-0,4
x=1

d)
0,15(2x+4)=2(1,3+0,3x)-0,6
0,3x+0,6=2,6+0,6x-0,6
0,3x-0,6x=2,6-0,6-0,6
-0,3x=1,4
x=-4⅔

e)
0,1(x+1)-0,05(3x-10)=0,4-0,35x
0,1x+0,1-0,15x+0,5=0,4-0,35x
0,1x-0,15x+0,35x=0,4-0,1-0,5
0,3x=-0,2
x=-⅔